Gynecological disorders in geriatric women regarding their frequency, diagnosis and management in the state of Himachal Pradesh, India - Sood, Nishi; Chandra, Parul; Dhiman, Bishan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Geriatric gynaecological problems have not received adequate attention in India. This study was undertaken to assess gynaecological disorders in geriatric women regarding their frequency, diagnosis and management in Himachal Pradesh, India. Methods: It was a prospective observational study of patients aged above 60 years, admitted in Gynecology ward, IGMC Shimla over one year. Spectrum of gynecological disorder, comorbidities, diagnosis and management were noted and analyzed. Results: 224 patients aged 60 years and above were admitted over a period of one year. The commonest presenting complaint was postmenopausal bleeding in 41.07% of patients. 80.80% patients had one or more comorbid conditions. Malignancy was the most frequent diagnosis 54% followed by uterovaginal prolapse in 30.35%. Ovarian cancer constituted 47.93% followed by cervical cancer 31.40%. 89.65% patients of ovarian cancer had surgical treatment whereas only 21.05% of cervical cancer patients underwent surgical treatment and rest were referred for radiation. In 62 out of 68 cases of pelvic organ prolapse had definitive surgical treatment. Conclusions: Pelvic organ prolapse and genital malignancy are the major gynecological causes of hospital admissions in the patients above 60 years. Ovarian and endometrial cancer are showing a rising trend in this age group. Cervical cancer was the second most common malignancy in this group and most of these patients presented at advanced stage. Therefore, recommendations to discontinue screening in older age groups must be viewed with caution.